The Impact Of The Lockdown Status On Student Learning During The Covid-19 Pandemic - Setiawan, Fiki; Taiman, Taiman (CV. Ridwan Publisher, 2020)
This study aims to describe the impact of the lockdown amid the COVID-19 outbreak on university students in West Java. An online survey was conducted from July 1 to July 8 2020. The structural questionnaire instrument used was the 'Google form' sent to students via WhatsApp and E-mail. A total of 231 students provided complete information regarding the survey. Simple percentage distribution is used to assess the learning status of study participants. During the lockdown period, around 70% of students were involved in e-learning. Most of the students use android phones to follow e-learning. Students have faced various problems related to anxiety depression, poor internet connectivity, and a low learning environment. Students from remote and marginalized areas, especially face significant challenges to learning during this pandemic. This study suggests targeted interventions to create positive spaces for learning among students as part of society. Strategies are urgently needed to build a sound education system during the pandemic to not interfere with student skills and productivity.